2009
DOI: 10.3852/08-097
|View full text |Cite
|
Sign up to set email alerts
|

New species ofStrophariafromAraucaria angustifoliaforests of southern Brazil

Abstract: Two new agaric species of Stropharia are described from Araucaria angustifolia (Brazilian pine) forests of southern Brazil. Stropharia agaricoides presents Agaricus-like basidiomes, small basidiospores (5-7 microm long) and pyriform cheilochrysocystidia. Stropharia venusta is characterized by the reddish to pinkish pileus, large basidiospores (12-15 microm long) and subclavate cheiloleptocystidia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…Observations. The proposed new species is another A. angustifolia forest inhabitant and, as other recently discovered taxa from this region, it shares some morphological similarities (Cortez & Silveira, 2007, 2008Silva et al, 2009). The presence of a brown pileus, the basidiospore features and the presence of cauloleptocystidia remind those of S. araucariae Cortez & R.M.…”
Section: Strophariasupporting
confidence: 54%
See 1 more Smart Citation
“…Observations. The proposed new species is another A. angustifolia forest inhabitant and, as other recently discovered taxa from this region, it shares some morphological similarities (Cortez & Silveira, 2007, 2008Silva et al, 2009). The presence of a brown pileus, the basidiospore features and the presence of cauloleptocystidia remind those of S. araucariae Cortez & R.M.…”
Section: Strophariasupporting
confidence: 54%
“…Recent taxonomic studies revealed unknown species from Asia (Senthilarasu & Singh, 2013;Tian & Bau, 2014), Australia (Chang et al, 2006), and America (Desjardin & Hemmes, 2001;Bandala et al, 2005). In Brazil, the genus is best known from the Atlantic Forest areas of southern and southeastern Brazil (Maia et al, 2015), and recent research in the southernmost state of Rio Grande do Sul resulted on the discovery of new taxa (Cortez & Silveira, 2007, 2008Silva et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fifty two specimens were studied, the majority were collected by the authors at the National Forest Dobrovolski et al (2006) and Silva et al (2009). Microscopic observations were made obtaining thin free-hand sections of the pileus and stipe of dried specimens, mounted on 5% KOH (potassium hydroxide) simple or with 1% Congo red solution.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, a series of studies on this family from Rio Grande do Sul improved the knowledge of the group with publications by Cortez & Coelho (2003, Cortez & Silveira (2007a, 2007b, Guzmán & Cortez (2004, 2005, Rossato et al (2009), Sobestiansky (2005), Silva et al (2006Silva et al ( , 2009 and Sulzbacher et al (2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation